Exploring the direct and mediating effect of transformational leadership on employee commitment - Dias, Á.; Silva, V.; Pereira, L.; Costa, R. L.; Gonçalves, R. (International Journal of Services and Operations Management, 2022)
The present study aims to correlate the concepts of organisational environment and employee commitment, having the concept of transformational leadership, and its role in organisations and subordinates, as an interlinked chain. In the context of the organisational environment, it’s important that companies are aware that it is through transformational leadership, and greater attention to the needs of their employees, that they will be able to last through time, resisting constant changes, inside and outside the company organisational environment, and keep employees in the organisation. A good leader is essential in an organisation because it maintains the harmony between the human needs and the organisation objectives, perpetuating the culture of the organisation and thus promoting the growth and success of both the company and its constituents. Human development must be seen by organisations as an organisational strategy and people management is part of this process. The results have showed that organisational environment has a significant and positive effect on transformational leadership and that transformational leadership has a significant and positive effect on organisational commitment.